Impact of a cervical dysplasia and its treatment on quality of life and sexual function - Heinzler, Judith Rebecca; Brucker, Janina; Bruckner, Thomas; Dinkic, Christine; Hoffmann, Janine; Dornhöfer, Nadja; Seitz, Stephan; Sohn, Christof; Rom, Joachim; Schott, Timm C.; Schott, Sarah (Archives of gynecology and obstetrics, 2018)
PurposeIn this case-control study, the impact on quality of life and sexual function in women with cervical dysplasia and conization will be evaluated, in order to address coping with such a premalignant lesion and to improve strategies for salutogenesis.MethodsThis multicenter case-control study evaluates women at special dysplasia outpatient clinic (T1) as well as 3 (T2) and 6 (T3) months after the diagnosis of a dysplasia. The women were subgrouped upon dysplasia only (S2) or dysplasia with conization (S1). Sexual function as well as cervix-related and general quality of life was assessed using validated instruments (FSFI-d, EORTC-QLQ-CX24, SF-36).ResultsWomen with dysplasia had a lower sexual functioning than controls (FSFI: S1: 23.8 ± 9.7 (p < 0.003); S2: 25.3 ± 7.5 (p < 0.03); K: 29.1 ± 4.5) as well as a lower physical component score (SF-36: S1: 51.3 ± 8.6 (p < 0.02); S2: 51.7 ± 7.8 (p < 0.05); K: 54.2 ± 6.6) and had a significantly reduced body image (EORTC-QLQ-CX24: S1: 75.7 (p < 0.001); S2: 76.5 (p < 0.001), K:89.2). Sexual functioning was not affected by conization in the observational period over 6 months; however, sexual worry was impacted. Over temporal progression women who underwent conization worried more. Regression analysis revealed a cervical dysplasia to impact sexual function.ConclusionData suggest that women with the diagnosis of a cervical dysplasia are impaired in their sexual function as well as general and cervix-related quality of life, mostly independent of conization or further observation. To improve salutogenesis in the long run, the communication on dysplasia and its treatment strategy at the beginning, as well as part of aftercare, or psychosomatic intervention, might be treatment options for women at risk.
Published online: 3 August 2018
Gesehen am 23.09.2019